The Impact of Organizational Climate in Realization Quality of Technical Education Technical Colleges in Sulymaniya Iraq - Kadhem F. Aaref; Jalal A. Mohamed (University of Science and Technology, Yemen, 2014)
The Impact of Organizational Climate in Realization Quality of Technical Education Technical Colleges in Sulymaniya Iraq                                                                                                     Abstract  This research deals with theme of relationship and impact between the dimensions of organizational climate and quality of education. The organizations of the Technical Education in Sulaimaniyah determined by the education colleges have been selected in order to be an arena for research procedures and test hypotheses. The research will be explored through the opinions of staff members which their numbers arrive(47).   The problem of the study began with a series of targeted questions which have been addressed to reveal the nature of the relationship between organizational climates represented as an independent variable dimensions and the quality of education as the dependent variable in the organizations surveyed. In order to achieve the objectives of this research, the research draws up a scheme adopted by default which reflects the nature of the correlations and impact between variables. Several key hypotheses and sub-hypotheses have been tested in this research through using statistical methods and group through a program Statistical Package for Social Sciences(SPSS). The research found a set of conclusions, including the presence of link relationships and significant impact between organizational climate in terms of dimensions and the quality of education in the organizations surveyed. As well as providing some necessary recommendations for public and private organizations surveyed, including senior management should take in technical colleges. The main attention have been paid to organizational structures and work on a fair incentive system and there will be more attention to the leadership pattern because of their role in the investigation to ensure the quality of education.